PENGARUH INDEPENDENSI, ETIKA DAN STANDAR AUDIT TERHADAP KUALITAS AUDIT INSPEKTORAT ACEH - Muhammad Kadhafi (Program Magister Akuntansi Unsyiah, 2013)
Objective of this study is to examine (1) the effects of independency, ethic and audit standard to audit quality (2) the effects of independency to audit quality (3) the effects ethic to audit quality (4) the effects of audit standard to audit quality. There are 32 respondents in this research taken from Internal Control Intitution in Aceh as Auditor. The methods is cencus, all elements of the population investigated individually in collecting data to obtain actual data. The hypothesis performed with multiple regression linear. The result show that: (1) independency, ethic and audit standard simultaneously have effects to audit quality (2) independency have effects to audit quality (3) ethic have effects to audit quality (4) audit standard have effects to audit qualityKeywords: Independency, Ethics, Audit Standard, Audit Quality